Analisis Bibliometrik: Pola Signifikansi dan Korelasi Penelitian Kepuasan Konsumen - Ela Laela; Septian Cahya Azhari (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2023)
This study identified patterns of significance and correlation in consumer satisfaction research across countries and became the subject of evaluation for future publications. The method used is bibliometric analysis. An analysis was conducted on 2,500 Dimensions.ai indexed publications, with the search keyword